Behaviour of the Portal Clotting Time in Cats Following the Intraduodenal Administration of Heparin - Kokot, Bogdan (Thrombosis and Haemostasis, 1973)
This work makes an attempt to display the behaviour of portal clotting time after intraduodenal administration of heparin. The experiments were carried out in 20 cats, which were divided into two groups.In the first stage of investigation the normal clotting time was determined in portal vein and caudal vena cava. Afterwards the same parameters were investigated after intraduodenal administration of heparin or saline solution.It was shown that after intraduodenal administration of heparin the clotting time in portal vein in each case was prolongated, but in the caudal vena cava it remains normal. After intraduodenal administration of saline solution the clotting time in both portal vein and caudal vena cava was unchanged.Conclusions. 1. In the performed experiments the heparin administered intraduodenally passes from the small intestine into the collection of the portal vein. 2. The lack of anticoagulative activity of the heparin given intraduodenally in the blood of the peripheral veins probably caused by a block present above the portal collection.